Influence of heat treatment on microstructure, mechanical properties, and corrosion behaviour of LM6 reinforced with copper powder - Aljermi, Almukhtar IB. A. (2021)
Copper (Cu) is one of the most widely used materials in the world. It has great significance in most industries, especially in the synthesis of alloys. A number of advanced Al-alloys have developed in which Cu is the main alloying element because it makes those alloys more heat treatable. Even though Al-Si eutectic casting alloy (LM6) has outstanding properties such as wear and corrosion resistance (CR), it has medium strength (130MPa) and is considered a non-heat-treatable alloy. Due to the importance of heat treatment for enhancing the mechanical properties of Al-alloys contained Cu, this study aimed to investigate the role of Cu in increase the effectiveness of heat treatment in changing the morphology structure of LM6 which in turn enhances the mechanical properties. In this research, the copper powder (Cup) was added to the LM6 to improve the hardness and tensile properties. By using the stir casting technique, Cup in the percentages of 3, 6, 9 wt.% has been added into the LM6. Some produced specimens were subjected to solution treatment (T6) to compare with the non-heat treated ones. The T6 was conducted at 490 0C for 6h followed by quenching in warm water (60 0C), then aging for 5h at 155 0C. The microstructures of the samples have been studied through optical microstructure, fracture surfaces of the tensile test samples were analysed via scanning electron microscopy, and X-Ray diffraction was used to identify chemical composition. Hardness and tensile strength tests were conducted for all samples. In order to study corrosion manner, samples were subjected to acidic and alkaline environments using the weight-loss method. The experimental result showed that the mechanical properties of LM6 were changed by adding a certain percentage of Cu and heat treatment through modifying the microstructure. It was observed that the maximum Rockwell hardness value (53.84 HRB) and highest tensile strength (152MPa) were achieved by applying heat treatment on the LM6 composite reinforced with 6wt.%Cu. On the other hand, the corrosion test showed that the LM6 composite reinforced with different Cu content had low CR than the LM6 as-cast. The corrosion test showed that LM6 as-cast and LM6 composite had higher CR in the acidic and alkaline solutions. Analysis of variance (ANOVA) has been used to determine the statistical significance of parameters that influencing the responses. The influence of Cu contents and heat treatment on the mechanical properties of LM6 composite have been evaluated by two-way ANOVA using statistical software Minitab 17. The statistical results revealed that interaction between the two factors, 6wt.%Cu and heat treatment, gave the optimal hardness and tensile properties.